The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.combustflame.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical effects of hydrogen addition on soot formation in counterflow diffusion flames: Dependence on fuel type and oxidizer composition

Abstract: We experimentally studied and kinetically modeled the effects of hydrogen addition on soot formation in methane and ethylene counterflow diffusion flames (CDFs). To isolate the chemical effects of hydrogen in such flames, we also ran a set of experiments on flames of the same base fuels but with the addition of helium. Specifically, we measured the soot volume fractions of the flames using the planar laser-induced incandescence technique. We simulated detailed sooting structures by coupling the gas-phase chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 94 publications
1
9
1
Order By: Relevance
“…It is also noticed that the overall SVF profile seems symmetric under the present X F /X O conditions. This situation is slightly different from the previous CDFs [44] (e.g., with X F = 1.0 and X O = 0.24), in which a skewed shape of the SVF profile (towards the fuel side) was observed. This is because the variations in the flame boundary conditions (X F /X O ) will alter the relative location of the flame sheet to the stagnation plane, which, in turn, will notably affect the soot evolution process and result in different axial distributions of SVF.…”
Section: General Flame Structure Of the Present Counterflow Flamescontrasting
confidence: 97%
“…It is also noticed that the overall SVF profile seems symmetric under the present X F /X O conditions. This situation is slightly different from the previous CDFs [44] (e.g., with X F = 1.0 and X O = 0.24), in which a skewed shape of the SVF profile (towards the fuel side) was observed. This is because the variations in the flame boundary conditions (X F /X O ) will alter the relative location of the flame sheet to the stagnation plane, which, in turn, will notably affect the soot evolution process and result in different axial distributions of SVF.…”
Section: General Flame Structure Of the Present Counterflow Flamescontrasting
confidence: 97%
“…The impact of H 2 on the formation of soot precursors and soot particles have also been the subject of numerous fundamental studies but mostly for mixtures of H 2 with fuels other than CH 4 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. By contrast, only a few similar studies, to the best of our knowledge, were addressed to characterize the impact of H 2 on the combustion of CH 4 flames [38][39][40][41]. Liu et al [38] and Xu et al [39] studied the effects of H 2 as a fuel additive (up to 40% comparing to the base fuel) on soot formation in diffusion CH 4 flames and showed that the addition of H 2 strongly decreases the formation of soot.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, only a few similar studies, to the best of our knowledge, were addressed to characterize the impact of H 2 on the combustion of CH 4 flames [38][39][40][41]. Liu et al [38] and Xu et al [39] studied the effects of H 2 as a fuel additive (up to 40% comparing to the base fuel) on soot formation in diffusion CH 4 flames and showed that the addition of H 2 strongly decreases the formation of soot. Ezenwajiaku et al [41] also investigated the impact of H 2 (added up to 20% in CH 4 ) on the formation of PAHs also in a diffusion flame.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the LII setup, a 10 Hz pulsed Nd-YAG laser with a fundamental emission at 1064 nm was used [ 50 , 59 , 60 ]. The laser beam was manipulated by a series of cylindrical lens to form a laser sheet (8 mm high) at the burner center.…”
Section: Methodsmentioning
confidence: 99%